The meaning of Laurier’s Advertising Message version #ThisistheGirlsway comfortable be yourself! on Youtube : (Charles Shanders Pierce Semiotic Analysis) - nuzhatussholehah, Nuzhatussholehah; Jamiati, Jamiati KN (COMMICAST, 2022)
Laurier's ad version of #ThisIsTheGirlsWay Comfortable Being Yourself takes a problem that often occurs in today's environment, and of course it is related to the Brand. This non-commercial advertisement is "soft-selling", that is, selling images (image-selling) instead of selling products (hard-selling/product selling). The meaning of the message in an advertisement like this can be expressed through understanding and interpreting the signs used in the advertisement. This study aims to determine the meaning of the message contained in the Laurier advertisement version of #ThisIsTheGirlsWay Comfortable Being Yourself. The theory in this study is the theory of marketing communication, verbal and non-verbal communication, advertising theory and advertising elements, message appeal, and Charles Shanders Pierce's semiotic theory. The research approach used is descriptive qualitative. Data collection techniques were carried out using interviews and literature studies. The results of the research obtained through women as objects have highlighted their character by visualizing clothing, expressions, and gestures as signs or so-called signs which are demonstrated according to the labels worn, so that all signs can reveal results or are called interpretants in the form of very meaningful messages. related to the signs that have been used. Thus expressing the meaning of the message that this advertisement invites women throughout Indonesia to be confident and not fixate on the labels that have been given by the surrounding community. Also, don't think that the word PMS is a negative thing, because PMS is a natural thing experienced by women. Be yourself and love yourself.